Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the inverse of the function [tex]\( y = 3x - 2 \)[/tex], we will follow these steps:
1. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
The idea of finding an inverse function is to find a function that will reverse the effect of the original function. To do this, we swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex].
Starting with [tex]\( y = 3x - 2 \)[/tex]:
[tex]\[ x = 3y - 2 \][/tex]
2. Solve for [tex]\( y \)[/tex]:
We need to isolate [tex]\( y \)[/tex] to find the inverse function.
- First, add 2 to both sides:
[tex]\[ x + 2 = 3y \][/tex]
- Next, divide both sides by 3:
[tex]\[ y = \frac{x + 2}{3} \][/tex]
3. Write the inverse function:
The inverse function is [tex]\( y^{-1}(x) = \frac{x + 2}{3} \)[/tex].
Now, we need to compare this result with the given options:
- [tex]\( y^{-1} = -\frac{2}{3}x + \frac{2}{3} \)[/tex]
- [tex]\( y^{-1} = \frac{2}{3}x - \frac{2}{3} \)[/tex]
- [tex]\( y^{-1} = \frac{1}{3}x + \frac{2}{3} \)[/tex]
- [tex]\( y^{-1} = -\frac{1}{3}x - \frac{2}{3} \)[/tex]
The correct inverse function we derived is:
[tex]\[ y^{-1}(x) = \frac{1}{3} x + \frac{2}{3} \][/tex]
Therefore, the correct option is:
[tex]\[ y^{-1} = \frac{1}{3} x + \frac{2}{3} \][/tex]
1. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
The idea of finding an inverse function is to find a function that will reverse the effect of the original function. To do this, we swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex].
Starting with [tex]\( y = 3x - 2 \)[/tex]:
[tex]\[ x = 3y - 2 \][/tex]
2. Solve for [tex]\( y \)[/tex]:
We need to isolate [tex]\( y \)[/tex] to find the inverse function.
- First, add 2 to both sides:
[tex]\[ x + 2 = 3y \][/tex]
- Next, divide both sides by 3:
[tex]\[ y = \frac{x + 2}{3} \][/tex]
3. Write the inverse function:
The inverse function is [tex]\( y^{-1}(x) = \frac{x + 2}{3} \)[/tex].
Now, we need to compare this result with the given options:
- [tex]\( y^{-1} = -\frac{2}{3}x + \frac{2}{3} \)[/tex]
- [tex]\( y^{-1} = \frac{2}{3}x - \frac{2}{3} \)[/tex]
- [tex]\( y^{-1} = \frac{1}{3}x + \frac{2}{3} \)[/tex]
- [tex]\( y^{-1} = -\frac{1}{3}x - \frac{2}{3} \)[/tex]
The correct inverse function we derived is:
[tex]\[ y^{-1}(x) = \frac{1}{3} x + \frac{2}{3} \][/tex]
Therefore, the correct option is:
[tex]\[ y^{-1} = \frac{1}{3} x + \frac{2}{3} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.